The contribution of the intra-firm exposures network to systemic risk - Victoria Landaberry; Fabio Caccioli; Anahi Rodriguez-Martinez; Andrea Barón; Serafin Martinez-Jaramillo; Rodrigo Lluberas (Latin American Journal of Central Banking (LAJCB), 2021)
We propose to use a systemic risk metric for an extended network which includes the inter-bank network, the banks-firms bipartite network, and the intrafirm exposures network in Uruguay. This is the first work, to the best of our knowledge, in which the intra-firm exposures network is estimated with good accuracy by using information from a firm survey. Given that the survey only includes the three most relevant debtors and creditors, we complete the full intra-firm exposures matrix by resorting to Maximum Entropy, Minimum Density and a new method which takes into account the known entries of the matrix obtained from the survey. We show that ignoring intra-firm exposures results in an important underestimation of systemic risk. Moreover, if the marginal liabilities are used as an indicator of the systemic relevance of firms, important network effects are ignored. To conclude, the paper contributes with a precise estimation of the impact of intra-firm exposures to overall systemic risk.
Keywords: 330; Bipartite network; Intrafirm network; RAS algorithm; Systemic risk